2016
DOI: 10.1101/067371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Scalable Data Access Layer to Manage Structured Heterogeneous Biomedical Data

Abstract: This work presents a scalable data access layer, called PyEHR, designed to support the implementation of data management systems for secondary use of structured heterogeneous biomedical and clinical data. PyEHR adopts the openEHR's formalisms to guarantee the decoupling of data descriptions from implementation details and exploits structure indexing to accelerate searches. Data persistence is guaranteed by a driver layer with a common driver interface. Interfaces for two NoSQL Database Management Systems are a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Authors concluded that Couchbase had better response times than MySQL, especially for larger datasets. Another study by [23] evaluated the scalability of PyEHR, a data access layer, using two NoSQL Database Management Systems: MongoDB and Elasticsearch, for secondary use of structured heterogeneous biomedical and clinical data. However, the un-structured aspect of data is not the focus of these studies.…”
Section: Related Workmentioning
confidence: 99%
“…Authors concluded that Couchbase had better response times than MySQL, especially for larger datasets. Another study by [23] evaluated the scalability of PyEHR, a data access layer, using two NoSQL Database Management Systems: MongoDB and Elasticsearch, for secondary use of structured heterogeneous biomedical and clinical data. However, the un-structured aspect of data is not the focus of these studies.…”
Section: Related Workmentioning
confidence: 99%